Netilmicin Pharmacokinetics After Single Intravenous Doses to Elderly Male Patients - Welling, Peter G. (1977)
The pharmacokinetics of the new aminoglycoside antibiotic netilmicin were examined after single intravenous injections at two different dose levels to elderly male patients. The durg obeyed two-compartment model kinetics in serum, and elimination was monoexponential from 1 to 2 h after dosing. Netilmicin levels in serum were above minimum inhibitory concentration values for most susceptible organisms for up to 8 h after dosing in normal individuals and for at least 12 h in uremic patients. Urine levels of netilmicin were uniformly above minimum inhibitory concentration values throughout 24 h after dosing. Netilmicin distribution characteristics were largely independent of both dose level and renal function. Netilmicin elimination kinetics were independent of dose level but were markedly influenced by renal function. Relationships are described between netilmicin elimination and renal function indicators, which provide a basis for dosage adjustment in individuals with renal function impairment.